The Whole is Greater than the Sum of Its Parts : Complementary Reforms to Address Microeconomic Distortions - Bergoeing, Raphael; Loayza, Norman V.; Piguillem, Facundo (Published by Oxford University Press on behalf of the World Bank, 2018)
This paper links microeconomic rigidities and technological adoption to propose a partial explanation for the observed differences in income per capita across countries. The paper first presents a neoclassical general equilibrium model with heterogeneous production units. It assumes that developing countries do not generate frontier technologies but can adopt them by investing in new capital, which requires firm renewal. The model analyzes how this process can be hindered by barriers to the entry of new investment projects and the exit of obsolete ones. It finds that there are nonlinearities in the way entry and exit barriers operate: Barriers have increasing costs, and they reinforce each other's negative impact. The paper then calibrates and simulates the model to measure the impact of these barriers on the GDP per capita gap between the United States and a large sample of developing countries. It accounts for a range of 26 to 60% of the income gap between the United States and 107 developing countries. Most importantly, the model implies that, for the median developing economy, about 50% of the simulated gap is explained by the interaction of entry and exit barriers (and the rest by their individual effects). The paper's main policy implication is that only comprehensive reforms can have substantial effects, especially when initial distortions are large. If they are too narrow (focusing on only one barrier) or too mild (leaving in place a large distortion), microeconomic reforms are unlikely to have significant effects on aggregate productivity and output growth.